Use of Badges as Achievements to Enhance Online Learning - B. V. Swaroop Raj; C. Divya (Archives of Medicine and Health Sciences)
Background and Aim: Digital badges are electronic symbols used as microcredentials to document achievement or skills mastered such as course completion, professional development participation, or training completion. The use of digital badges is trending upward in higher education. This study was undertaken for digital badge creation and implementation and investigated the effects of a digital badge system, on three aspects of undergraduate learners: levels of intrinsic motivation, participation in online learning, and general attitudes toward digital badges. This study aimed to implement digital badges for online learning by medical undergraduates and evaluate student perception regarding digital badges. Materials and Methods: A study was conducted on 150 students of 1st MBBS 2020–2021 batch. WordPress platform was used to design website with additional plugins for registration, discussion forum, and achievement badges. Students were sensitized to digital badge system. Students gained points for posting replies to online discussion, viewing content and clarifying doubts, answering quizzes, and online submission of assignments. Using the points scored, a scale was designed for awarding badges. Student feedback on Likert scale and perception regarding satisfaction, and motivation toward academics by digital badges were collected and analyzed. Results: Participants had positive perceptions of the badges, finding them authentic and innovative. The respondents agreed that digital badges helped to set goals and motivated to achieve these goals. Most students who earned digital badges agreed that badges helped increase their confidence in course material (78%), focus on specific learning objectives (65%), look deeper into course competencies (71%), and motivated to attend online classes regularly (83%). Conclusion: The digital badges were positively received by students who commented favorably about digital badges in their learning. Digital badges were perceived by students as a positive adjunct to learning and may provide a novel mechanism to enhance online learning.